Econometric Evaluation of Crude Oil Price Effects on the Economy’s Wellbeing: A Case of South Africa - Mtshali, Siphesihle Mduduzi; Niyimbanira, Ferdinand (International Journal of Energy Economics and Policy, 2025)
Changes in crude oil prices are seen as a significant contributor to macroeconomic uncertainties globally. Crude oil is a vital resource for most emerging economies and an energy source used to transport goods and to generate electricity. This points out that the economic wellbeing of crude oil importing countries rely significantly on imported oil, making the nations susceptible to crude oil price increases. The study evaluates crude oil price effects on the economy’s wellbeing of South Africa. The evaluation used unemployment and economic growth as proxies of the economy’s wellbeing of the country, with data spanning from 1994Q1 to 2023Q4 for unemployment model and from 1993Q1 to 2024Q1 for economic growth model. Both models have the same independent variables, which include crude oil prices, inflation, exchange rate, and interest rate. The study employed an EGARCH model and the Toda-Yamamoto causality test, and the results indicate that crude oil prices drive both unemployment and economic growth, which proves that the ongoing changes in crude oil prices on the world market has a substantial influence on the economy’s wellbeing of South Africa, influencing both unemployment and the nation’s economic growth. The study recommends that policymakers from oil-importing countries consider investment in renewable energy sources. By diversifying its energy portfolio, South Africa can improve energy security and mitigate the risks linked to supply interruptions or geopolitical conflicts.